Selective Carbanion–Pyridine Coordination of a Reactive P, N Ligand to RhI. Issue 15 (12th February 2019) - Devillard, Marc; Ehlers, Andreas; Siegler, Maxime A.; van der Vlugt, Jarl Ivar
Abstract: Ligands with reactive carbon sites in the periphery of a metal center have emerged as a powerful approach for metal–ligand bond activation. These reactive carbon sites are commonly generated by deprotonation strategies. Carbon–silicon bond cleavage is a potential alternative to access such constructs. Herein, the monodesilylation of bis‐silyl‐substituted P, N scaffoldPN Si2 in the coordination sphere of [Rh I (Cl)(CO)(PN Si2 )] (1 ) with sodium azide is disclosed. This affords a unique dinucleating anionic κ 2 ‐ C, N ‐κ 1 ‐ P ligand with a carbanionic methine carbon atom directly bound to rhodium as part of a four‐membered Rh‐N‐C‐C rhodacycle. This dimer undergoes meta ‐pyridine C−H activation facilitated by weak bases, which leads to a desymmetrization of the system and provides a σ, π‐bridging 3‐pyridyl fragment bound to Rh I . The facile Si−C cleavage strategy may pave the way to studying the reactivity and functionalization of a variety of κ 2 ‐ C, N ‐coordinated pyridine scaffolds for selective transformations. Abstract : To C or not to C : The first selective P, N ‐to‐ C, N ligation switch in the coordination sphere of a transition metal (see figure), induced by site‐selective C−Si cleavage in the ligand backbone by means of NaN3, is reported. The carbanionic methine fragment generated in situ displaces phosphorus as donor to the Rh I center with formation of a highly strained four‐membered Rh‐N‐C‐C metallacycle, stabilized by dimerization involving phosphane coordination to the neighboring rhodium center.